The Research Value of Chinese Traditional Music for the Development of Sports Universities - Han Yupeng, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The integration of Chinese traditional music into sports universities presents a unique opportunity to address the intrinsic challenges of compositional technique loss, limited audience reach, and constrained dissemination, as well as the external influences of a culture and education system dominated by Western paradigms. Sports universities, as critical centers for cultural preservation and innovation, are uniquely positioned to protect and transmit Chinese musical traditions. By leveraging their regional, systematic, specialized, and informational advantages, these institutions can significantly enhance the continuity and vitality of Chinese traditional music. This paper explores the adaptation of heritage methodologies to the context of sports universities. Using Beijing Sports University as a case study, we examine the implementation and outcomes of integrating traditional music into sports education. The university's approach includes leveraging scientific research, new national policies, and information technology to support traditional conservation. Furthermore, the curriculum development and heritage programs are specifically tailored to enhance extracurricular education and the cultivation of talent in sports contexts. Activities such as the formation of music and art societies, along with unique writing and performance initiatives, play a pivotal role in disseminating traditional music and shaping participant engagement. We also highlight the innovative practices developed at sports universities for promoting traditional music, including new methods of content delivery and independent innovations in heritage techniques. These initiatives not only preserve the rich musical heritage of China but also add a unique dimension to the educational experience and athletic training at sports universities, fostering a more culturally enriched environment that enhances both academic and athletic pursuits.